Identifying the factors influencing track degradation on the UK rail network - Clarke, S.; Prescott, Darren (2017)
As trains traverse track, the smoothness of its vertical geometry decreases. This degradation is linked to many interrelated factors, making it difficult to identify the primary causes. Through the use of multiple layer analysis, each factor was individuated and nonparametric hypothesis tests utilised. These showed that speed, sleepers and rail joint type have the largest impact on degradation rate. Rail type was seen to be less important than discussed in the literature. The impact of bedrock was more dependent on porosity than stiffness. The importance of minimising fines in the ballast was shown by the negative effect of dirty traffic.